PERANCANGAN APLIKASI PEMUTAR MUSIK BESERTA PENAMPIL LIRIK MUSIK BERBASIS ANDROID (Information Technology and Telematics, 2016)
Abstract Music is something that can not be separated from humans. Now music has been like a necessity of human life. Wherever they are, they want listen to music that can make calm or increase the spirit. The music is not far from the lyrics of the song, if there are no lyrics, the music did not exist. Most people do not understand the lyrics of the music heard. To facilitate people and music lovers in playing music and displaying the lyrics of the songs wherever they are then be made Application Music Player along Viewer Lyrics. In displaying the lyrics using a scraping technique Lyrics. Scraping technique is a technique for cutting the HTML page and retrieve the needed information. To display the lyrics needed an internet connection, because the lyrics are taken from the website www.azlyrics.com. Making Music Player app using Android Studio, and runs on the android operating system minimum 4.1 (Jelly Bean). Keywords : Music, Lyrics, Music Player, Scraping Technique Lyrics, Android